2016
DOI: 10.4081/rt.2017.6541
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Instability in Medullary Carcinoma of the Colon

Abstract: Medullary carcinoma (MC) of the large intestine is a relatively new histological type of adenocarcinoma characterized by poor glandular differentiation and an intraepithelial lymphocytic infiltrate. MC can be associated to a defective mechanism for DNA mismatch repair, caused by the so-called microsatellite instability (MSI). We present the case of a 44 years old Caucasian woman, who referred to the Emergency Room with symptoms mimicking an acute appendicitis. Computed tomography and colonoscopy demonstrated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
(10 reference statements)
1
7
0
1
Order By: Relevance
“…However, this could not be concluded from a single case and it could be of value to compare MC cases with different FOXP3 positive cell counts. In a recent published analogous to this case report [18] the clinical and histological findings were equivalent to those presented herein, having similar free of disease period (24 and 28 months, respectively) despite there being no post-surgical treatment in our case. However, the T-cell subgroups of the microenvironment were not mentioned in that case.…”
Section: Discussionsupporting
confidence: 88%
“…However, this could not be concluded from a single case and it could be of value to compare MC cases with different FOXP3 positive cell counts. In a recent published analogous to this case report [18] the clinical and histological findings were equivalent to those presented herein, having similar free of disease period (24 and 28 months, respectively) despite there being no post-surgical treatment in our case. However, the T-cell subgroups of the microenvironment were not mentioned in that case.…”
Section: Discussionsupporting
confidence: 88%
“…The other type of the colorectal cancer with dense lymphoid stroma is medullary carcinoma (MC). Colorectal MC is a rare disease, only 10 cases reported in the literature to date; colorectal MC is almost always associated with a microsatellites instability-high (MSI-H) status [25][26][27][28][29][30][31][32][33] ( Table 2). Thirunavukarasu et al [34] reported that MC was a rare tumor, accounting for approximately 5-8 of every 10,000 colon cancers diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…MC is twice as prevalent in middle-aged women, favors the right side of the colon, and has a lower risk of lymph node metastasis than colon adenocarcinoma. MC can be poorly differentiated (72%) or undifferentiated (22%) with solid sheets of cells and excessive intraepithelial lymphocytic infiltration [ 2 ]. It does not have the glandular structure seen in adenocarcinoma [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…MC can be poorly differentiated (72%) or undifferentiated (22%) with solid sheets of cells and excessive intraepithelial lymphocytic infiltration [ 2 ]. It does not have the glandular structure seen in adenocarcinoma [ 2 ]. Only a few cases of metastatic MC have been published in the literature [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation